1999
DOI: 10.1152/ajprenal.1999.277.5.f756
|View full text |Cite
|
Sign up to set email alerts
|

Thiazide induces water absorption in the inner medullary collecting duct of normal and Brattleboro rats

Abstract: The reduction of urinary volume after the use of thiazide in the treatment of diabetes insipidus (DI) is known as the "paradoxical effect." Since enhanced proximal solute and water reabsorption only partially account for the reduction in urinary volume, an additional diuretic effect on nephron terminal segments was postulated. Thus the aim of our work was to investigate the effect of hydrochlorothiazide (HCTZ) on water transport in the inner medullary collecting duct (IMCD) of normal and Brattleboro rats. Osmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 32 publications
2
36
0
1
Order By: Relevance
“…Therefore, the Li-induced AQP2 downregulation was partially (from 20 to 40% of normal controls) reversed by chronic HCTZ treatment. Recently, an in vitro microperfusion study performed by Cesar and Magaldi (11) showed that HCTZ increased osmotic and diffusional water permeabilities in inner medullary collecting duct from normal rats (in the absence of vasopressin) and from Brattleboro rats. Our results suggest that the increase in water permeability induced by HCTZ in NDI should not be limited to the inner medullary collecting duct because our AQP2 immunohistochemistry in cortex showed the similar pattern to that in inner medulla (Figure 3).…”
Section: Hctz Treatment Partially Reverses Li-induced Aqp2 Downregulamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the Li-induced AQP2 downregulation was partially (from 20 to 40% of normal controls) reversed by chronic HCTZ treatment. Recently, an in vitro microperfusion study performed by Cesar and Magaldi (11) showed that HCTZ increased osmotic and diffusional water permeabilities in inner medullary collecting duct from normal rats (in the absence of vasopressin) and from Brattleboro rats. Our results suggest that the increase in water permeability induced by HCTZ in NDI should not be limited to the inner medullary collecting duct because our AQP2 immunohistochemistry in cortex showed the similar pattern to that in inner medulla (Figure 3).…”
Section: Hctz Treatment Partially Reverses Li-induced Aqp2 Downregulamentioning
confidence: 99%
“…In addition, the possibility that thiazide diuretics can directly affect water permeability in the collecting duct epithelium was suggested (10), and a recent in vitro microperfusion study reported that HCTZ enhanced water absorption in inner medullary collecting duct from normal rats and from Brattleboro rats (11).…”
mentioning
confidence: 99%
“…Interestingly, in these experiments, addition of prostaglandins diminished the effect of thiazides, possibly explaining why prostaglandin synthesis inhibitors (e.g. indomethacin) augment the effect of thiazides in DI (17).…”
mentioning
confidence: 81%
“…Furthermore, functional studies by Shirley et al (12) and Gronbeck et al (16) suggested that water reabsorption downstream of the proximal tubule must also contribute to the antidiuresis seen after prolonged thiazide treatment of central DI. Cesar and Magaldi reported that hydrochlorothiazide (HCTZ) is able to directly increase the water permeability in inner medullary collecting ducts isolated from normal or Brattleboro rats and perfused in vitro (17). Interestingly, in these experiments, addition of prostaglandins diminished the effect of thiazides, possibly explaining why prostaglandin synthesis inhibitors (e.g.…”
mentioning
confidence: 98%
“…Thus, there is less delivery of fluid to the collecting duct, resulting in a lower urine output. However, some studies indicate that there may also be a more direct effect of thiazides to increase water permeability of collecting duct principal cells (30,76).…”
Section: Nephrogenic Diabetes Insipidusmentioning
confidence: 99%